Light-Emitting Diode Illumination Enhances Biomass, Pigment, and Lipid Production in Halotolerant Cyanobacterium Aphanothece halophytica - Sitthichai Thongtha; Chokchai Kittiwongwattana; Aran Incharoensakdi; Saranya Phunpruch (My University, 2025)
Light characteristics, including spectrum and intensity, significantly impact cyanobacterial biomass production, pigment biosynthesis, and cellular metabolism, influencing the composition of various biochemical compounds. This study aimed to investigate the effects of light-emitting diode (LED) illumination on biomass, pigment, and lipid production in the unicellular halotolerant cyanobacterium Aphanothece halophytica, cultivated in a suitable natural seawater (SNSW) medium. The results revealed that LED light outperformed fluorescent light, with blue LED light, particularly at an intensity of 60 μmol photons m−2 s−1, significantly enhancing growth, pigment synthesis, and lipid accumulation. This resulted in a maximum cell density of 68.96 ± 1.52 × 106 cells mL−1, a specific growth rate of 0.302 ± 0.002 day−1, and a lipid productivity of 56.81 ± 0.75 mg L−1 day−1. White LED light produced lipids suitable for biodiesel, whereas blue, green, and red LEDs promoted the accumulation of polyunsaturated fatty acids (PUFAs), beneficial for food supplements. These findings highlight the potential of LED-based cultivation strategies for optimizing biomass and biochemical compound production in A. halophytica.
Keywords: Halotolerance; Algal biology and biofuel production